Insulin Secretion Capacity as a Crucial Feature to Distinguish Type 1 From Type 2 Diabetes and to Indicate the Need for Insulin Therapy – A Critical Discussion of the ADA/EASD Consensus Statement on the Management of Type 1 Diabetes in Adults - Fritsche, Andreas (Experimental and Clinical Endocrinology & Diabetes, 2023)
In the recently published consensus statement on the treatment and management of type 1 diabetes issued by experts from the American (ADA) and European (EASD) diabetes societies, measurement of endogenous insulin secretion using fasting C-peptide is recommended as a diagnostic criterion. In contrast, our group recently suggested fasting C-peptide/glucose ratio (CGR) for the determination of endogenous insulin secretion. In addition, this ratio may turn out as a potential decision aid for pathophysiologically based differential therapy of diabetes. In this comment, the following points will be discussed: i) CGR as the basis of differential diagnosis of type 1 diabetes, ii) CGR as the basis of treatment decisions for or against insulin in diabetes, and iii) the ease of application of CGR in clinical practice. The use of CGR may complement the ADA/EASD recommendations and should provide a practical application in clinical practice.
Keywords: insulin secretion; c-peptide; treatment; classification